Amphiphilic Antimony(V) Complexes for Oral Treatment of Visceral Leishmaniasis - Fernandes, Flaviana R. (American Society for Microbiology, 2013)
The need for daily parenteral administration is an important limitation in the clinical use of pentavalent antimonial drugs against leishmaniasis. In this study, amphiphilic antimony(V) complexes were prepared from alkylmethylglucamides (L8 and L10, with carbon chain lengths of 8 and 10, respectively), and their potential for the oral treatment of visceral leishmaniasis (VL) was evaluated. Complexes of Sb and ligand at 1:3 (SbL8 and SbL10) were obtained from the reaction of antimony(V) with L8 and L10, as evidenced by elemental and electrospray ionization-tandem mass spectrometry (ESI-MS) analyses. Fluorescence probing of hydrophobic environment and negative-staining transmission electron microscopy showed that SbL8 forms kinetically stabilized nanoassemblies in water. Pharmacokinetic studies with mice in which the compound was administered by the oral route at 200 mg of Sb/kg of body weight indicated that the SbL8 complex promoted greater and more sustained Sb levels in serum and liver than the levels obtained for the conventional antimonial drug meglumine antimoniate (Glucantime [Glu]). The efficacy of SbL8 and SbL10 administered by the oral route was evaluated in BALB/c mice infected with Leishmania infantum after a daily dose of 200 mg of Sb/kg for 20 days. Both complexes promoted significant reduction in the liver and spleen parasite burdens in relation to those in the saline-treated control group. The extent of parasite suppression (>99.96%) was similar to that achieved after Glu given intraperitoneally at 80 mg of Sb/kg/day. As expected, there was no significant reduction in the parasitic load in the group treated orally with Glu at 200 mg of Sb/(kg day). In conclusion, amphiphilic antimony(V) complexes emerge as an innovative and promising strategy for the oral treatment of VL.